The Influence of Work Engagement on Employee Performance with Organizational Commitment as an Intervening Variable in Correctional Institution Employees - Tan Evan Tandiyono; Garaldine Alyana Nathahuru (International Journal of Economics, Commerce, and Management, 2024)
This study is a quantitative research. The purpose of this research is to analyze the influence of work engagement on employee performance with organizational commitment as an intervening variable. The subjects of this study are the employees of Class IIA Correctional Facility in Sidoarjo. The sampling technique used in this study is a census, where data is obtained from the entire population. The data collection method involves a questionnaire containing 44 questions. The respondents in this study consist of 107 employees in the production department. Data analysis is conducted using SPSS. The results of this study indicate that work engagement influences organizational commitment, organizational commitment influences performance, and work engagement influences performance. Furthermore, organizational commitment cannot mediate the influence of work engagement on performance.